The RABBIT risk-based approach to clinical implementation of new technology: SRS as a case study. (June 2020) - Ralston, Anna; Graham, Peter; Poder, Joel; Yuen, Johnson
Abstract: Radiation oncology technology continues to evolve rapidly, resulting in advanced versions frequently being brought to market. Before a new product is used standard tests are carried out to reduce the risks associated with failure of the equipment to comply with well-established technical specifications. It is much harder to identify and reduce the risks associated with how the new technology is used clinically, such as those related to poor communication and high workload. To ensure that new technology and techniques are used safely and appropriately the implementation project should be managed by a multidisciplinary team (MDT) made up of representatives from all the relevant professions. The MDT's role is to agree on the project scope, identify and rank all risks and benefits, and direct resources towards mitigating the highest risks. Before clinical release there should be consensus from the MDT that the benefits of the new technology outweigh the residual risks. The introduction of initiatives to optimise current practice may involve major changes which can be met with barriers such as limited support from management, insufficient time for MDT meetings, and staff fearful of being shown to have poor practices. To help overcome these challenges our team at St George Hospital Cancer Care Centre has developed a Risk and Benefit Balance Impact Template (RABBIT), which guides an MDT through the rapid implementation and safe use of new technology and techniques with an easy to follow Microsoft Word document. The implementation of stereotactic radiosurgery is used as a case study to illustrate the RABBIT methodology. The RABBIT is a user-friendly method for a busy radiotherapy clinic to transition to a risk-based MDT approach for the implementation of new technologies and techniques. When staff from all disciplines feel empowered to raise concerns about risks the workplace become inherently safer for patients and staff alike.